2016
DOI: 10.1186/s12936-016-1419-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effective use of mosquito nets in the prevention of malaria in some parts of Mezam division, Northwest Region Cameroon

Abstract: BackgroundIn Cameroon, malaria continues to be endemic and the first major cause of morbidity and mortality among the most vulnerable groups—children under 5 years of age, pregnant women, people living with HIV/AIDS and the poor. The use of long-lasting insecticide-treated bed nets (LLINs) is one of the recommended measures to prevent malaria. The present study was aimed at accessing the acceptability and effective use of LLINs on the prevalence of malaria in PMI Nkwen, Bambui and its environs.MethodsHospital-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
49
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 14 publications
14
49
4
1
Order By: Relevance
“…As a result, this negative attitude would perpetuate the morbidity and mortality emanated from the disease. These results are compatible with other studies conducted in Ghana, Gambia, Cameroon, and Tanzania, which found low utilization of mosquito nets [12][13][14].…”
Section: Discussionsupporting
confidence: 92%
“…As a result, this negative attitude would perpetuate the morbidity and mortality emanated from the disease. These results are compatible with other studies conducted in Ghana, Gambia, Cameroon, and Tanzania, which found low utilization of mosquito nets [12][13][14].…”
Section: Discussionsupporting
confidence: 92%
“…The high patronage of the ITNs may have resulted in the much reduced malaria prevalence recorded amongst the respondents (27.1%) as compared to 86.7% prevalence recorded amongst those who reported as not using ITNs. This finding is similar to that of Ntonifor and Veyufambom in Cameroon who reported a low prevalence amongst pregnant women and children who had the ITNs and were found to also utilize them [11]. This confirmed the assertion of Nzayirambaho et al [12] and Adeneye et al [13] that stated that on control measures to reduce malaria, the most promising measure is the use of ITNs and curtains.…”
Section: Discussionsupporting
confidence: 81%
“…The use of indoor spatial repellents, such as a mosquito-repellent bed nets, represents another frequently-cited personal protective behavior against mosquito-borne disease. 12,17 Window and door screens are also recommended mechanisms for reducing exposure while indoors. 13,14 Among travelers to high-risk malaria destinations, approximately half report intention of using a mosquito net.…”
Section: Introductionmentioning
confidence: 99%